Strengthening international collaboration through pre- clinical elective research - Wan Mohamad Zain, Wan Nor I’zzah; Abdul Rahman, Amirah; Ibahim, Mohammad Johari; Hisham, Nur Syafina; Hairul Anuar, Nurul Fathiah; Ibrahim Mze, Asma Ali; Mohd Idris, Ros Akmal (Faculty of Medicine, 2026)
The Faculty of Medicine, Universiti Teknologi MARA (UiTM), through the Institute of Medical Molecular Biotechnology (IMMB), hosted medical students from Universitas Abdurrab, Pekanbaru, Riau, Indonesia, for an elective research attachment under the ongoing Memorandum of Understanding (MoU) between UiTM and Universitas Abdurrab. The programme aimed to strengthen academic collaboration while providing meaningful research exposure to medical students.